DEFINING MARKETING FOR THE NEW CENTURY - Setia Budhi Wilardjo (Value Added : Majalah Ekonomi dan Bisnis, 2016)
Marketing is an organizational function and a set of processes for creating, communicating, and delivering value to customers and for managing customer relationships in ways that benefit the organization and its stakeholders. Marketing management is the art and science of choosing target markets and getting, keeping, and growing customers through creating, delivering, and communicating superior customer value. Marketing are skilled at managing demand: they seek toinfluence its level, timing, and composition for goods, services, events, experiences, persons, places, properties, organizations, information, and ideas. They also operate in four different marketplaces, consumer, business, global, and nonprofit. Marketing is not done only by the marketing department. It needs to affect every aspect of the customer experience. To create a strong marketing organization, marketers must think like executives in other departments, andexecutives in other departments must think more like marketers. Today’s marketplace is fundamentally different as a result of major societal forces that have resulted in many new consumer and company capabilities. These forces have created new opportunities and challenges and changed marketing management significantly as companies seek new ways to achieve marketing excellence.    Keywords : marketing, marketing management, the new century